Keanekaragaman Makrofauna Tanah sebagai Bioindikator Kualitas Tanah di Lahan Penimbunan Sampah Kota Semarang dengan Variasi Kondisi Lingkungan - Arifa Marsanda Widyandini; Sri Ngabekti; Amnan Haris (Jurnal Riptek, 2026)
Soil macrofauna play an important role in maintaining soil quality and fertility, including through improving aeration, water absorption, and the dispersal and decomposition of organic matter. The presence of macrofauna is also an effective biological indicator to assess soil conditions ecologically. This study aims to assess soil quality based on the diversity of macrofauna species found in landfill areas in Semarang City. The approach used was quantitative method with sampling technique using pitfall trap at three points of observation location. Based on the identification results, 11 species of macrofauna were found with a total of 85 individuals. The diversity index value in diurnal and nocturnal communities showed a medium category, indicating a fairly good species diversity although uneven. The average index values for both time groups were relatively equal, reflecting the stability of the macrofauna community in the two periods of daily activity. Sites with good natural vegetation tended to have higher soil quality, while areas directly exposed to landfill activities showed degraded soil quality due to lack of vegetation cover and high inorganic waste content.